2004
DOI: 10.1179/003258904225015545
|View full text |Cite
|
Sign up to set email alerts
|

Effects of porosity on delamination wear behaviour of sintered plain iron

Abstract: Haynes.1 The presence of pores is accompanied by a decrease in strength and ductility as well as a detrimental in uence The role of porosity on the wear behaviour of sintered on conductivity and magnetic properties.2 Meanwhile the iron was investigated. Sintered iron was used in initial attempts for mechanical characterisation of sintered preference to steel because the various alloy additions materials were focused on static tests. However, in order and matrix heterogeneity in the latter might aVect the to fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
36
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(40 citation statements)
references
References 10 publications
3
36
0
1
Order By: Relevance
“…P/M parts generally have more than 5 vol% porosity which is a limiting factor for increased usage of P/M materials for structural components. It is generally believed that the presence of porosity negatively influence the mechanical properties of the materials [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…P/M parts generally have more than 5 vol% porosity which is a limiting factor for increased usage of P/M materials for structural components. It is generally believed that the presence of porosity negatively influence the mechanical properties of the materials [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The strengthening of sintered P/M low alloy steels can be achieved through densification, alloying and heat treatment 3 . The wear mechanisms of P/M alloy steel parts has similar properties compared to wrought materials, under the same tribological conditions, but the porosity plays a significant role in wear behaviour of alloy steels 4,5 . Wang et al 6 reported that quenched and tempered Mo-based low alloy P/M steel preforms has higher wear coefficient values compared to assintered preforms and also their sliding wear characteristics is considerably influenced by heat treatment.…”
Section: Introductionmentioning
confidence: 89%
“…Chen et al [18] investigated the influence of porosity on composite materials and suggested that porosity may help to absorb the impact energy that accompanies crack splitting. Simchi and Danninger [19] showed that porosity acts as lubricant reservoirs in wet sliding conditions, which provides a considerable advantage in wear process.…”
Section: Introductionmentioning
confidence: 99%